A survey on the prevalence and the risk factors analysis of blood parasite infections in fighting bulls in Sukhothai province - Senachai, Kamonthip; Mapongpeng, Roipim; Promkuntod, Naruepol; Saenkum, Nunnapat; Thaduang-ta, Chaiyakorn (Journal of Mahanakorn Veterinary Medicine, 2024)
The purposes of this study were to examine the prevalence and the risk factors of blood parasite infections in fighting bulls in five districts of Sukhothai province: Muang Sukhothai, Khiri Mat, Thung Saliam, Kong Krailat, and Sri Samrong between May and September 2023. Two hundred and fifty-one cattle blood samples were collected from 134 farms, submitted to Veterinary Research and Development Center (Lower Northern Region), examined by thin blood smear and Woo's method. The questionnaire was used to collect data for analyzing the risk factors of blood parasite infections. The results revealed the presence of 3 types of blood parasites including Microfilaria, Theileria spp. and Trypanosoma evansi. The herd prevalence was 2.24% (95% CI: 0.76-6.38), 1.49% (95% CI: 0.41-5.28), 0.75% (95% CI: 0.13-4.11). Individual prevalence was 1.20% (95% CI: 0.41-3.45), 0.80% (95% CI: 0.22-2.86), 0.4% (95% CI: 0.07–2.22), respectively. The study also found that farms equipped with mosquito nets had a lower prevalence of blood parasite infections with an odds ratio (OR) = 0.08 (95% CI: 0.01 - 0.4, p-value = 0.0006). It is crucial to increase farmers' awareness about improving housing structures to prevent blood-sucking insects, thereby reducing the risk of blood parasite infections in fighting bulls and minimizing economic losses.